An update on trends in the types and quality of childhood immunization research outputs from Africa 2011–2017: Mapping the evidence base. (11th April 2019) - Haddison, Eposi C.; Machingaidze, Shingai; Wiysonge, Charles S.; Hussey, Gregory D.; Kagina, Benjamin M.
Highlights: Update of an analysis used to synthesise data on childhood immunisation in Africa. PubMed and Africa Wide databases were searched from January 2011 to September 2017 for articles on childhood immunisation. There was a remarkable increase in immunisation output from 2011 to 2017 compared to the previous decades. Most studies focused on the EPI and a majority of the studies were generated by Nigeria and South Africa. There is need for collaboration between high and low research generating countries to foster research on the continent. Abstract: Background: Strengthening immunisation programmes in Africa remains a key strategy of improving vaccine coverage. Research plays a vital role in the design and implementation of strategic immunisation plans for improving vaccination coverage, in turn providing context specific evidence to inform policy and practice. We therefore updated an evidence map describing the types and quality of available literature on childhood immunisation in Africa from 2011 to 2017. Methods: PubMed and Africa Wide databases were searched for English studies on childhood immunisation in Africa published from January 2011 to September 2017. Studies had to be conducted in humans and the reported information needed to be on either: vaccines; immunisation programmes; immunisation policies; or epidemiology of vaccine preventable diseases targeted by Expanded Programme on Immunisation vaccines. Results: Out of 5567 studies retrieved, 797 studies from 165 journals met the inclusion criteria. During 2011–2017, 42 African countries contributed to research on childhood immunisation. Most studies were carried out in multiple countries (15.1%). Five countries contributed 41% of the total research output. Nigeria and South Africa contributed the highest proportion of studies at 12% and 11.4% respectively. The quantity of research output increased progressively from 2011 to 2015 after which there was a significant decline. Conclusion: There was a remarkable increase in childhood immunisation research in the period 2011 to 2017 when compared to the initial assessment. However, the reason for decline in research output from 2015 requires further investigation. Most childhood immunisation research was still generated by five countries as previously observed, highlighting the critical need for strategic investment in research capacities and improved collaboration between countries in Africa.